(untitled) (Research, Society and Development, 2021)
Introduction: Hypodermoclysis, also called subcutaneous therapy, is an alternative infusion route, which aims to administer solutions and drugs. This route has the same efficacy as the intravenous route, with the advantage of being less painful and with rare adverse events. However, it is still a procedure little implemented and discussed by health professionals. Objective: To map scientific productions on the use of hypodermoclysis by health professionals. Methodology: This is a scoping review, guided by the PRISMA Extension for Scoping Reviews instrument. Searches were performed in five databases. The results were presented descriptively, with the presentation of graphs and tables. Results: Twenty-seven studies were included, most of them developed by Brazilian nurses, published in 2016 and 2019, in Portuguese, which sought to assess the main indications and adverse reactions regarding hypodermoclysis. Conclusions: This scoping review offers evidence of the role of nursing in the performance of hypodermoclysis and the advancement of knowledge in this area. In addition to compiling information that can guide health professionals to use this technique, in order to ensure the success of therapy and patient safety.